Characteristics of multiple transpolar arcs motion and its corresponding magnetospheric dynamic process - Sun, Yan-Ju; Zhang, Qing-He; Xing, Zan-Yang; Wang, Xiang-Yu; Zhang, Duan; Tang, Bin-Bin; Lu, Sheng; Ma, Yu-Zhang; Wang, Yong; Xiu, Zhi-Feng; Chen, Xin-Ming; Xu, Tong; et al. (Frontiers in Astronomy and Space Sciences, 2025)
Multiple Transpolar arcs (MTPAs) are distinct auroral phenomenon occurring in the high-latitude ionosphere under prolonged northward interplanetary magnetic field (IMF) conditions. While the evolution of MTPAs is thought to be mainly modulated by the IMF By, the underlying physical mechanisms driving their dynamics remain insufficiently understood. This study integrates space-based and ground-based observations, and magnetohydrodynamic (MHD) simulations to investigate the evolution and characteristics of MTPAs and their associated field-aligned currents (FACs). The observations results reveal that following a sudden change in the IMF By orientation from dawnward to duskward, MTPAs exhibit a pronounced motion towards the duskside, driven by the strong positive IMF By. Concurrently, flow shears are detected on both flanks of the auroral arcs. MHD simulations under similar conditions demonstrate that flow shears emerge at the low-latitude boundary layer (LLBL) of the magnetosphere, facilitating plasma trapped from the magnetosheath and central plasma sheet onto open magnetic field lines. This plasma is subsequently transported into the lobe regions, generating upward FACs that accelerate local particles and form auroral arcs migrating towards the duskside within the polar cap. These findings advance our understanding of the magnetosphere-ionosphere coupling processes under varying IMF conditions.